PENGARUH KARAKTERISTIK INDIVIDU GENERASI MILENIAL, NILAI BUDAYA GENERASI MILENIAL DAN KARAKTERISTIK KEWIRAUSAHAAN TERHADAP PERILAKU KEWIRAUSAHAAN UMKM DI KOTA BANJARMASIN - Basuki Basuki; Rahmi Widyanti; Mohammad Zainul; Idzani Muttaqin (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The success of an entrepreneur, including millennial entrepreneurs, in carrying out their business activities is inseparable from their internal characteristics and the cultural values that surround them.The purpose of this study is to examine and analyze the partial and simultaneous influence of individual characteristics of the millennial generation, millennial cultural values, and entrepreneurial characteristics on the entrepreneurial behavior of millennial-generation Small and Medium Enterprises (SMEs) in Banjarmasin City.The study location in Banjarmasin City has 36,781 MSMEs. Sampling was conducted using a purposive sampling technique with a sample of 150 MSMEs with the following conditions: MSMEs represent millennial-generation small and medium enterprises with business capital ranging from Rp 1,000,000 to Rp 300,000,000; Data analysis was performed using SPSS for Windows 21.The results of this study indicate a partial and simultaneous influence of individual characteristics of the millennial generation, millennial cultural values, and entrepreneurial characteristics on the entrepreneurial behavior of millennial-generation Small and Medium Enterprises (SMEs) in Banjarmasin